Phase Transfer Catalyzed Preparation of 4-Methylbenzenesulfonyl Imidazole for Regioselective Synthesis of Mono-6-(4-methylbenzenesulfonyl)-β-cyclodextrin - I Wayan Muderawan; I Wayan Mudianta; Made Kurnia Wiastuti Giri (Universitas Gadjah Mada, 2022)
The preparation of 4-methylbenzenesulfonyl imidazole by using triethylamine as an effective phase‐transfer catalyst (PTC) under mild biphasic conditions has been studied intensively. The method can be used for large-scale preparation with high purity and high yield of 4-methylbenzene-sulfonyl imidazole. The result in 4-methylbenzenesulfonyl imidazole has been successfully applied for the regioselective synthesis of mono-6-(4-methylbenzenesulfonyl)-β-cyclodextrin in an aqueous medium. This synthetic methodology concept, together with the synthetic versatility of PTC, provides a general and reliable general strategy for the practical and industrial regioselective synthesis of highly valuable mono-6-(4-methylbenzenesulfonyl)-β-cyclodextrin as a key intermediate for the single functional isomer mono-substituted cyclodextrin derivatives. As characterized by FTIR, NMR and mass spectrometry, mono-6-(4-methylbenzenesulfonyl)-β-cyclodextrin was obtained in high purity.